Before and after Bourdieu: the trajectory of the sociology of culture in Brazil - do Nascimento Arruda, Maria Arminda (2026)
The relevance of Pierre Bourdieu's work for contemporary sociology is unquestionable. In the specific case of the sociology of culture in Brazil, this importance is equally notable and dates back to the internationalization program of Bourdieusian sociology and its reception in the country through some mediators in national sociology from the 1970s onwards, especially in São Paulo. Based on a review of the available literature and on the collective discussion of the authors' experience in research with diverse cultural objects (social thought, literature, cinema, music), this text seeks to offer a critical overview of the formation and trajectory of the sociology of culture in Brazil, which can be organized into two moments: a before and an after of Bourdieu's reception. In doing so, it aims to problematize this rupture and reflect on the importance of such theoretical reference for the field in the country, pointing out its merits, such as the contribution to the expansion and consolidation of research, as well as its analytical limits, such as the secondarization of the specific forms and languages of each cultural object.